Bioremediation using microbial fuel cell for polluted marine sediment - Pribadi, Tri Dewi Kusumaningrum; Rosada, Keukeu Kaniawati; Ihsan, Yudi Nurul; Rossiana, Nia (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.